Interpreting the Gospels and Acts : an exegetical handbook - Turner, David L. (Grand Rapids, MI, Kregel Academic, 2019)
In this volume of the Handbooks for New Testament Exegesis series, David Turner provides a comprehensive guide for interpreting and conveying the Gospels and the book of Acts. Key background information such as literary genres, historical setting, and theological themes lay the groundwork for properly reading these five books. This is followed by practical guidance on textual issues and original-language exegesis of passages from the Gospels and Acts. Interpreting the Gospels and Acts is an essential resource for anyone teaching and preaching these foundational books.
The genre and structure of the Gospels and Acts -- The historical setting of the Gospels and Acts -- The theology of the Gospel and Acts -- Preparing to interpret the Gospels and Acts -- Interpreting passages in the Gospels and Acts -- Communicating passages in the Gospels and Acts -- From text to sermon: Two examples -- Selected resources.
Includes bibliographical references (pages 323-353).
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible; Bible; Criticism, interpretation, etc